1992
DOI: 10.1577/1548-8675(1992)012<0585:lhfcsb>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Lake Huron Fish Community Structure Based on Gill-Net Catches Corrected for Selectivity and Encounter Probability

Abstract: This paper describes the depth distributions and numeric abundance of fishes in the Canadian waters of Lake Huron based upon size‐corrected results of experimental netting from 1958 through 1968. Gill‐net catches were corrected for encounter probabilities based on the positive correlation between fish size and swimming speed and for retention probability offish of different sizes once they encounter the net. A 3‐parameter gamma function was used to fit net‐selectivity curves for 13 Great Lakes species. Compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 15 publications
1
33
0
Order By: Relevance
“…The feeding habit of the fish (piscivorous) could be responsible for its size. Some researchers have used fish size to estimate the relative probability that fish of various sizes will encounter the nets (Rudstam et al 1984;Spangler and Collins 1992). Comparatively, the food consumed by the populations of H. fasciatus in Tarkwa bay and the Lagos lagoon in Nigeria (Ugwumba 1988) consisted principally of fish.…”
Section: Discussionmentioning
confidence: 99%
“…The feeding habit of the fish (piscivorous) could be responsible for its size. Some researchers have used fish size to estimate the relative probability that fish of various sizes will encounter the nets (Rudstam et al 1984;Spangler and Collins 1992). Comparatively, the food consumed by the populations of H. fasciatus in Tarkwa bay and the Lagos lagoon in Nigeria (Ugwumba 1988) consisted principally of fish.…”
Section: Discussionmentioning
confidence: 99%
“…Nets were set overnight (5.00 p.m-7.00 a.m) and during the following day (7.00 a.m-12.00 p.m). Indeed, gill-net selectivity depends on the probability that the fish meets the net and the probability that the fish was caught and retained in the net (a function of the circumference of the fish's head and of the mesh size of the gill-net) (Spangler and Collins, 1992). Many fish assemblage descriptors were considered as possible index metrics.…”
Section: > Fish Sampling and Fish Assemblage Descriptorsmentioning
confidence: 99%
“…Similarly, the EFL-girth relation for 58 preseason males (r 2 = 0.74; P < 0.001) was used to predict girth measurements for 65 other preseason males. For many species, maximum gillnet selectivity corresponds to G:P ratios centered around 1.1-1.4 (e.g., Spangler and Collins, 1992;Van Den Avyle et al, 1995) and some authors have concluded that the optimum girth is about 1.25× the mesh perimeter (e.g., Hamley, 1980). We created frequency-distributions of G:P ratios in each mesh to see whether the ratios fell within expected ranges.…”
Section: Discussionmentioning
confidence: 99%